RANCANG BANGUN MEDIA INTERAKTIF TATA CARA SHALAT SUNNAH DAN WUDHU BERBASIS ANDROID - Yova Wijaya (PROCEEDING STIMA)
Prayer is one of the obligations for Muslims who have been said to be able to pray and must be done both for believers and on the way. But before praying, you must have ablution, because ablution is one of the conditions for the validity of prayer. Tazkia Insani Jatipamor Elementary School Majalengka helps the learning process by developing technology, especially in the field of Android-based multimedia, so Tazkia Insani Elementary School students will know more about the use of multimedia displays that are designed and modified appropriately so that children will understand and understand faster. Just like on a computer, smartphones can also be installed in various applications that are desired. The interactive media on the procedure of Sunnah prayer and ablution based on Android can also be an alternative to learning so that it is expected to increase the interest of children to enjoy learning and applying it in their daily lives.